PENGARUH INSENTIF PAJAK, CAPITAL INTENSITY DAN UKURAN PERUSAHAAN TERHADAP KONSERVATISME AKUNTANSI - Intan Fitria; Ani Kusumaningsih (Publika Citra Media, 2026)
This study aims to analyze and provide empirical evidence regarding the effect of tax incentives, capital intensity, and company size on accounting conservatism in infrastructure sector companies listed on the Indonesia Stock Exchange for the period 2019-2023. The study uses a descriptive quantitative method, and the data analysis was performed using E-Views version 13. The sample was obtained using a purposive sampling method. The sample consists of 10 infrastructure companies with a 5-year observation period, resulting in a total of 50 financial report data points for analysis. The results of the study show that tax incentives, capital intensity, and company size, when considered together, affect accounting conservatism. Tax incentives do not have an effect on accounting conservatism, capital intensity affects accounting conservatism, and company size also affects accounting conservatism.